Genetic literacy series: Primer part 2—Paradigm shifts in epilepsy genetics. (9th May 2018) - Helbig, Ingo; Heinzen, Erin L.; Mefford, Heather C.; ,
Summary: This is the second of a 2‐part primer on the genetics of the epilepsies within the Genetic Literacy Series of the Genetics Commission of the International League Against Epilepsy. In Part 1, we covered types of genetic variation, inheritance patterns, and their relationship to disease. In Part 2, we apply these basic principles to the case of a young boy with epileptic encephalopathy and ask 3 important questions: (1) Is the gene in question an established genetic etiology for epilepsy? (2) Is the variant in this particular gene pathogenic by established variant interpretation criteria? (3) Is the variant considered causative in the clinical context? These questions are considered and then answered for the clinical case in question.